The Influence of Thinking Styles on Students’ Critical Thinking in Biology Learning Using Research-Based e-LKPD - Jayanti Syahfitri; Meti Herlina (STAI Hubbulwathan Duri, 2025)
Thinking styles represent individuals’ preferred ways of processing and solving problems, which may influence the development of higher-order thinking such as critical thinking. In the digital era, learning environments supported by technology, such as research-based electronic worksheets (e-LKPD), can accommodate diverse thinking styles and foster critical thinking. This study aimed to examine the influence of thinking styles on students’ critical thinking skills in biology learning assisted by e-LKPD. A total of 112 high school students were selected through random sampling. Data were collected using the Yanpiaw Creative-Critical Thinking Styles (YCCTS) instrument and a standardized critical thinking skills test. Regression analysis was employed to measure the relationship between thinking styles and indicators of critical thinking, including interpreting, analyzing, applying, evaluating, and concluding. The regression results indicated a significant relationship between thinking styles and critical thinking skills (p 0.05). The R² values demonstrated strong predictive power across all indicators: interpreting (82.4%), analyzing (85.7%), applying (81.6%), evaluating (85.5%), and concluding (79.9%). Students with dominant critical thinking styles showed higher scores in critical thinking tests compared to those with balanced or creative styles. These findings suggest that thinking styles can serve as predictors of students’ critical thinking performance. Moreover, the use of research-based e-LKPD provides a supportive learning environment that enhances the expression of thinking styles, thereby strengthening critical thinking skills. Integrating digital, research-based learning resources is an effective strategy to align with students’ thinking styles and promote critical thinking in science education.